Improving the Learning Outcomes of Class V Students at SD Negeri 5 Wakorumba Selatan Operational Material on Fractions Through the Application of Peer Tutors - hasri hasri (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
The purpose of this study was to improve the ability of fifth-grade students of SD Negeri 5 Wakorumba Selatan in solving fractional number operations story problems through a peer tutor approach. The type of research is classroom action research. The implementation of this classroom action research consists of 2 cycles. The procedures of this research are (1) planning, (2) action implementation, (3) observation and evaluation, (4) reflection. The data sources of this research consist of students and teachers. The data types obtained are quantitative and qualitative data through observation sheets, learning outcomes tests, and journals. How to collect data about learning situations is obtained through observation sheets, learning outcomes data are taken by giving tests to students, and data about self-reflection and changes in class are obtained through journals. Results showed that the results of the initial test to the first cycle of action that received a minimum score of 6.0 increased by 7.69%, and from the results of the first cycle of action test to the second cycle of action which brought a minimum score of 6.0 increased by 23.08%. Fifth-graders at SD Negeri 5 Wakorumba Selatan to solve operations story problems can be improved through a peer tutor approach.